ZMIERZCH BILINGWIZMU I JEGO SKUTKI - Widła, Halina (Neofilolog, 2016)
The purpose of this article is to show different approaches and trends in foreign language teaching in Polish schools over the last two decades. Emphasis will be placed on changing the skills and competencies needed to succeed to transition from the bilingual to the multilingual citizen. European population is becoming more and more multicultural, with a growing diversity of cultures, races, values, and languages. The article also presents some examples of research with regard to attitudes and stereotypes. It is observable that this phenomenon exerts impact on the effective classroom management. Taking into account the new context of work in foreign language classrooms, the author focuses on strategies and key challenges encountered by teachers such as: differences in motivation or interests, individualization resulting from the biography of a language, cultural baggage, linguistic interference, and implementation of new technologies.